2
$\begingroup$

Mathematica shows that the infinite series

\begin{align}\sum _{i=0}^{\infty } \rho ^i \prod _{j=1}^i \left(\frac{\alpha }{j}+1\right)= -\frac{(1-\rho )^{-\alpha }}{\rho -1}. \end{align}

How do I prove this?

$\endgroup$
  • $\begingroup$ Starting from the rhs, using the binomial expansion and long division would show it. But, I suppose that you want to start from the lhs, isn't it ? $\endgroup$ – Claude Leibovici Jan 16 '15 at 11:04
1
$\begingroup$

Assuming the series converges, we have

\begin{align} & \sum_{i = 0}^\infty \rho^i \prod_{j = 1}^i \left(\frac{\alpha}{j} + 1\right)\\ &= \sum_{i = 0}^\infty \rho^i \prod_{j = 1}^i \frac{\alpha + j}{j}\\ &= \sum_{i = 0}^\infty \rho^i \frac{(\alpha + 1)(\alpha + 2)\cdots (\alpha + i)}{i!}\\ &= \sum_{i = 0}^\infty (-1)^i \rho^i \frac{(-\alpha - 1)(-\alpha - 2)\cdots (-\alpha - i)}{i!}\\ &= \sum_{i = 0}^\infty (-\rho)^i \binom{-\alpha-1}{i}\\ &= (1-\rho)^{-\alpha-1}\\ &= \frac{(1-\rho)^{-\alpha}}{1-\rho}. \end{align}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.